219k views
4 votes
Please help with this using the chain rule

Please help with this using the chain rule-example-1
User Akn
by
5.2k points

1 Answer

7 votes

Answer:

a is the answer

Explanation:

y = ( x^2 +2x+ 5 )^6,

let u be equal to x^2 + 2x + 5

y = u^6 '

dy|du = 6u^5, du|dx = 2x + 2

dy|dx = dy|du × du|dx = 6u^5 ×( 2x + 2 )

= 2( x + 1) × 6u^5 = 12 ( x + 1 )( x^2 + 2x +5)^5

User Awad Maharoof
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.